Childbirth experience of mothers attending selected secondary hospital - Moni, Mahfuja Khatun; Tripty, Nabila Nusrat; Sarmin, Tanjina; Joty, Afroza Tasnim; Suchona, Sadia Haque; Tamanna, Tanjeemay; Begum, Fakrunnesa; Biswas, Gayatree (International Journal of Research in Medical Sciences, 2024)
Background: Childbirth experience is an important event in every woman’s life but there is lack of current research in this area in Bangladesh. For improving quality of care for pregnant women during childbirth, clinical care modalities should be designed to improve the experience of care by the mothers. The aim of the study was to assess the childbirth experience in regards to respectful maternity care, effective communication, companionship during childbirth and continuity of care. Methods: A cross-sectional study was conducted between January to December 2020 among 98 mothers during facility-based childbirth in one model district hospital and one existing district hospital situated in northern part of the country. Results: Mean age of the respondents was 23.2 years (+SD 5.0). Majority completed secondary education (53.1%), and their average monthly family income was 12081.63 taka (+SD 5469.08). Childbirth experience was not associated with socio-demographic status and educational background (P>0.05). This study presents data on physical abuse prevalence and consent refusal rates among respondents, stratified by age groups, educational levels, and monthly family income. Despite variations observed across demographics, statistical analysis, including chi-square tests with continuity correction, revealed no significant differences (P<0.05) in these outcomes based on demographic factors. Conclusions: More than half of the mothers experienced non consented care and around one fourth of mothers being physically abused during childbirth.